Analytic Solutions of the Thomas Equation by Generalised Tanh and Travelling Wave Hypothesis Methods - Al-Ghafri, Khalil Salim (International Journal of Applied Mathematical Research, 2013)
The analytical solutions of the Thomas equation are investigated. The wave transformation is exploited to simplify the Thomas equation from a form of partial differential equation (PDE) to an ordinary differential equation (ODE). Both of the generalised tanh and the travelling wave hypothesis methods are applied to obtain exact solutions for the Thomas equation.